2016
DOI: 10.1037/pag0000069
|View full text |Cite
|
Sign up to set email alerts
|

A picture is worth a thousand words? Not when it comes to associative memory of older adults.

Abstract: Properties of the binding mechanism in associative recognition were studied by examining the influence of the pictorial superiority effect on the age-related associative deficit. The informative aspect of associative recognition is the recollection of the pairing. Previous findings indicate that recollection is susceptible to aging and that pictorial presentation can enhance recollection and facilitate associative recognition. Pictorial presentation was found to facilitate item recognition by both young and ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…A possible reconciliation may be differences in the strategic encoding of word versus picture pairs with the latter perhaps evoking more spontaneous unitization (e.g., imagining the person in the scene in Chen and Naveh-Benjamin’s material), which would allow for familiarity-supported associative memory that is dependent on regions external to the hippocampus (Haskins, Yonelinas, Quamme, & Ranganath, 2008). This fits with evidence for enhanced associative recognition of picture pairs compared with word pairs in a previous study (Guez & Lev, 2016; but note that this did not hold for older adults). As we are not aware of any research comparing rates of spontaneous unitization of word versus picture pairs, this possible reconciliation remains speculative for now.…”
Section: Discussionsupporting
confidence: 91%
“…A possible reconciliation may be differences in the strategic encoding of word versus picture pairs with the latter perhaps evoking more spontaneous unitization (e.g., imagining the person in the scene in Chen and Naveh-Benjamin’s material), which would allow for familiarity-supported associative memory that is dependent on regions external to the hippocampus (Haskins, Yonelinas, Quamme, & Ranganath, 2008). This fits with evidence for enhanced associative recognition of picture pairs compared with word pairs in a previous study (Guez & Lev, 2016; but note that this did not hold for older adults). As we are not aware of any research comparing rates of spontaneous unitization of word versus picture pairs, this possible reconciliation remains speculative for now.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown that associative memory (i.e., memory for how different units of information are related) declines more with age than item memory (Chalfont & Johnson, 1996). This has been shown across various methods and materials, such as person-action pairs (Old & Naveh-Benjamin, 2008a), word pairs (Naveh-Benjamin, 2000), and picture pairs (Guez & Lev, 2016). According to the Associative Deficit Hypothesis (ADH; Naveh-Benjamin, 2000), older adults are particularly impaired on tests of associative memory because the mechanism that binds individual items into pairs at encoding declines with age (Old & Naveh-Benjamin, 2008b).…”
Section: Introductionmentioning
confidence: 97%
“…Following these findings, the ADH predicts that older adults will perform more poorly on tasks that require the formation of associations between items within an episode or scene. Multiple studies have shown that older adults demonstrate an associative deficit for different types of pairs, such as word-word pairs (Naveh-Benjamin, 2000; Provyn, Sliwinski, & Howard, 2007), picture-picture pairs (Guez & Lev, 2016; Naveh-Benjamin, Hussain, Guez, & Bar-On, 2003), and face-name pairs (Naveh-Benjamin, Guez, Kilb, & Reedy, 2004; for a review, see Old & Naveh-Benjamin, 2008).…”
mentioning
confidence: 99%